“They are here. They are everywhere. They are us.” – Posthuman Encounters in Samanta Schweblin’s Little Eyes (2018) - Missler, Heike (Journal of Posthumanism, 2024)
In Samanta Schweblin’s novel Little Eyes (2018), the latest technological hype that stretches across the globe comes in the shape of cute, pet-like little robots with cameras for eyes. These so-called kentukis are remotely inhabited and controlled by their human users via an online connection which is established at random. As the novel’s blurb - “They are here. They are everywhere. They are us.” - suggests, a kentuki is at once a familiar and unfamiliar creature and users’ experiences range from comforting to unsettling. The novel revolves around the theme of stranger danger and reports several uncanny encounters between humans and not-quite-humans in places around the world, both from the perspective of the kentukis’ owners (so-called keepers) and the voyeurs (so-called dwellers).